Evidências de validade do diagnóstico de enfermagem “Autogestão ineficaz do linfedema” em mulheres mastectomizadas - Oliveira, Juliana Maria Barbosa Bertho de (Universidade Federal de Goiás, 2024)
Introduction: The nursing diagnosis (ND) “Ineffective Self-Management of Lymphedema” (000278) is defined as unsatisfactory management of symptoms, treatment regimen, physical, psychosocial and spiritual consequences, and lifestyle changes inherent to living with edema related to obstruction or dysfunction of lymph nodes or lymphatic vessels, which may be evidenced in the population of women who have undergone mastectomy. Validation studies refer to the degree to which evidence and theories support the interpretation of a diagnosis as well as its defining characteristics. Thus, studies of this nature are necessary for better utilization of the nursing diagnosis in nursing practice. Objective: To verify the validity evidence of the nursing diagnosis “Ineffective Self-Management of Lymphedema” in women who have undergone mastectomy. Method: This is a methodological study, divided into two different stages. The first stage refers to concept analysis, according to the Walker and Avant model (2011), conducted between July and August 2022, with an update in February 2023. The second stage refers to content validation conducted from July to October 2023, using a semi-structured questionnaire sent online to 80 judges. Fifty-two specialist judges agreed to participate. The study was approved by the Research Ethics Committee, CAAE nº 63063922.0.0000.5078. The elements judged in the content analysis were evaluated for their relevance to the ND Ineffective Self-Management of Lymphedema. To assess the relevance of the components of the ND, the Aiken's V coefficient (V ≥ 0.09) was applied for content validation with a confidence interval (95%) for each item. The Cronbach's alpha index was 0.96, used to analyze the consistency of the judges' evaluations. Results: In the first stage of the study, concept analysis, through eight steps, attributes, antecedents, and consequences were identified from a literature review analyzing 43 articles, and a model case and a contrary case were constructed. The 51 terms described and identified as a result of the conceptual analysis were submitted to validation by specialist judges in the second stage, content analysis. The terms “psychological and cognitive limitations” for associated conditions and “mastectomized women” as a population at risk were validated. The specialist judges also suggested the inclusion of the term “breast cancer survivors” for the at-risk population, “access to healthcare services,” and “lack of medical information” as elements of related factors. Twenty- eight terms, among defining characteristics and related factors, were considered valid for the ND Ineffective Self-Management of Lymphedema: psychological suffering, interference in work and daily activities, decreased quality of life, concern with appearance and aesthetics, muscle weakness, progression of swelling, dysfunction of the affected limb, loss of self-esteem, occupational suffering, embarrassment/shame, sensation of heaviness, physical discomfort, use of clothing to conceal swelling, pain, physical limitations, excess weight, psychological suffering, negative experiences with compression garments, psychological and cognitive limitations, self-care deficits, treatment costs, lack of resources for self-care, difficulty integrating physical exercise and drainage into daily routine, lack of knowledge about self-care, limitations in knowledge about lymphedema, knowledge about lymphedema management, and absence of training for self-care. Conclusion: Through concept analysis, it was possible to identify fundamental elements for understanding the concept of Lymphedema Self-Management, while also identifying the need for tools that evaluate this nursing diagnosis in women who have undergone mastectomy, to assist in identifying the elements validated by the judges during content analysis. A limitation is the lack of similar studies for comparison of results which points to the need for the inclusion of new elements that can contribute both to increasing the level of evidence of the ND proposed by the NANDA-I taxonomy and to establishing and developing standardized language for nursing that is useful for clinical practice. Thus, it is suggested that this study be followed up with clinical validation, to apply the findings in women who have undergone mastectomy.